The Effectiveness of Rice for the Prosperous Population Program and Non-Cash Food Assistance (Case Study in Sikayu Village, Buayan Sub-district, Kebumen District) - Rezqyana Ayu Pertiwi; Raden Rara Aulia Qonita; Joko Sutrisno (Caraka Tani: Journal of Sustainable Agriculture, 2019)
Food aid program policy is made to overcome poverty problem in Indonesia. This policy always changes year by year to improve the effectiveness of the program. This research aims to determine the effectiveness of Rice for the Prosperous Population Program (Bansos Rastra) and Non-Cash Food Assistance (BPNT) in Sikayu Village, Buayan Sub-district, Kebumen District, Central Java Province with 6T indicators or 6 indicators of accuracy, including accurate on target, accurate on price, accurate on amount, accurate on time, accurate on quality and accurate on administration. The basic method of this research is descriptive method. The location of this research is determined intentionally. Sampling is done by purposive sampling technique. The analysis was carried out using the results criteria approach. The effectiveness of Bansos Rastra program is based on Bansos Rastra General Guidelines 2018, while the effectiveness measurement of BPNT program is based on BPNT General Guidelines 2018. The effectiveness of Bansos Rastra program, which is based on the achievement of the objectives according to Bansos Rastra General Guidelines 2018, is said to be ineffective as there is one out of the four points of purpose which is not achieved, namely the point of aid distribution conducted every month. The effectiveness of BPNT program in Sikayu Village based on the 6T indicator reaches 100% since all indicators have been fulfilled. The effectiveness of BPNT program based on the goals achivement is in accordance with BPNT General Guidelines 2018 which is said to be effective as all objectives have been achieved.